RESPON PERTUMBUHAN DAN HASIL TANAMAN KEMANGI (Ocimum sanctum L) TERHADAP PEMBERIAN PUPUK ORGANIK DAN ARANG SEKAM SEBAGAI MEDIA TANAM - Prayoga Mahmud S; Palupi Puspitorini; Army Dita Serdani; Alvita sekar Sarjani; Agung Setya Wibowo (Universitas Islam Balitar, 2023)
This research was conducted to determine the response of growth and yield of Basil (Ocimum Sanctum L.) to the application of organic fertilizer and husk charcoal as a planting medium. This study used a factorial Randomized Block Design (FRBD) which was designed using 2 factors and was repeated 3 times. Factor 1 is the application of organic Petroganik fertilizer with 3 levels, namely: P1 = 5 g/plant. P2= 5.5 g/plant. P3= 6 g/plant. While factor 2 is the provision of husk charcoal as a planting medium with 3 levels, namely: A1 = Soil and husk charcoal 3:1. A2= Soil and husk charcoal 2:2. A3= Soil and husk charcoal 1:3. From these two factorials, 9 treatment combinations were obtained. The treatment was repeated 3 times and obtained 27 treatment combination units. The variables observed included plant height, number of leaves, number of branches, and fresh weight. The results of the analysis of variance showed that there was a significant effect on the combination of treatment with husk charcoal as a planting medium and the addition of organic fertilizer on all observation variables (plant height, number of leaves, number of branches, and fresh weight).